Identification of the Pathogen Causing Stem Blight Disease on Chili in Sindangjaya Village, Cipanas, Cianjur, West Java Based on Morphological and Molecular Analyses - Wartono Wartono (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2021)
Chili (Capsicum annuum L.) is a vegetable commodity with high economic value which is widely cultivated by farmers in Indonesia. One of the obstacles faced in chili cultivation is stem rot disease. This study aimed to identify the pathogens that caused stem rot in chili plants obtained from one location in Sindangjaya Village, Cipanas District, Cianjur Regency, West Java Province based on morphological and molecular analyses. Pathogen identification was performed with morphological and molecular approaches. The morphological characters observed included colony shape, sporangium diameter, and mating type. The pathogenicity of the isolates was assayed by inoculating chili stems aged 40 days. Molecular identification was carried out using two pairs of primers for ITS regions and TEF-1 gene. Based on the results of morphological and molecular identification, as well as pathogenicity tests, it was confirmed that Phytophthora capsici pathogen was the causal agent of stem rot in chili plants collected from Sindangjaya Village. Further study is needed to determine the spread of the disease, damage, and yield loss caused by stem rot disease, as well as how to prevent and control the disease.